Colorism’s Impact On Dark-Skinned African-American Women’s Self-image - Belouadah, Samia (My University, 2022)
Colorism is a global phenomenon. It is the discriminatory favor of light skin over dark skin. This academic work focuses on Colorism in the African American community. Specifically African American women. This dissertation explores colorism’s impact on dark skinned African-Americans self-image. This research aims to try to prove how dark skinned African American women’s exposure to colorism has caused them to have a negative image of themselves. An analytic study will be done in order to try to prove the latter statement through the novels; “The Bluest Eye” (1970) by Toni Morrison and “The Skin I’m in” (1998) by Sharon G. Flake.
Case Study: Toni Morrison's “The Bluest Eye” (1970) and Sharon Flake's “The Skin I'm in” (1998)
Keywords: Colorism; African-American; Impact; community; Self-image; Dark-skinned; women